Genetic structure of Pyrenophora teres net and spot populations as revealed by microsatellite analysis - Leišová-Svobodová, Leona; Minaříková, Věra; Matušinsky, Pavel; Hudcovicová, Martina; Ondreičková, Katarína; Gubiš, Jozef (Fungal biology, 2014)
The population structure of the fungal pathogen Pyrenophora teres, collected mainly from different regions of the Czech and Slovak Republics, was examined using a microsatellite analyses (SSR). Among 305 P. teres f. teres (PTT) and 82 P. teres f. maculata (PTM) isolates that were collected, the overall gene diversity was similar (ĥ = 0.12 and ĥ = 0.13, respectively). A high level of genetic differentiation (FST = 0.46; P < 0.001) indicated the existence of population structure. Nine clusters that were found using a Bayesian approach represent the genetic structure of the studied P. teres populations. Two clusters consisted of PTM populations; PTT populations formed another seven clusters. An exact test of population differentiation confirmed the results that were generated by Structure. There was no difference between naturally infected populations over time, and genetic distance did not correlate with geographical distance. The facts that all individuals had unique multilocus genotypes and that the hypothesis of random mating could not be rejected in several populations or subpopulations serve as evidence that a mixed mating system plays a role in the P. teres life cycle. Despite the fact that the genetic differentiation value between PTT and PTM (FST = 0.30; P < 0.001) is lower than it is between the populations within each form (FST = 0.40 (PTT); FST = 0.35 (PTM); P < 0.001) and that individuals with mixed PTT and PTM genomes were found, the two forms of P. teres form genetically separate populations. Therefore, it can be assumed that these populations have most likely undergone speciation.
Keywords: Ascomycota; genotyp; Genotype; mikrosatelitní repetice; Česká republika; mykologické určovací techniky; genetická variace; Microsatellite Repeats; Czech Republic; Cluster Analysis; Genetic Variation; Slovakia; molekulární typizace; Molecular Typing; Slovenská republika; Hordeum vulgare; SSR; Mycological Typing Techniques; fylogeneze; PTM; PTT; Drechslera teres; Phylogeny; shluková analýza